2007
DOI: 10.1111/j.1471-4159.2007.05205.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal NTS1 receptors regulate nociceptive signaling in a rat formalin tonic pain model

Abstract: Central administration of the neuropeptide neurotensin (NT) was shown to induce antinociceptive responses both spinally and supraspinally. Although NTS2 receptors play an important role in modulating the activity of spinal neurons, we have recently implicated NTS1 receptors in NT's analgesic effects in acute spinal pain paradigms. The current experiments were thus designed to examine the antinociceptive effects of intrathecal administration of NTS1 agonists in formalin‐induced tonic pain in rats. We first esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 86 publications
(208 reference statements)
7
73
0
Order By: Relevance
“…There is now compelling evidence demonstrating that the high-affinity NTS1 subtype is involved in antinociception (Wustrow et al, 1995, Smith et al, 1997, Urban and Gebhart, 1997, Buhler et al, 2005, Sarret et al, 2005, Buhler et al, 2008, Roussy et al, 2008. Thus, microinjection of the selective NTS1 agonist PD149163 into the rostral ventromedial medulla produced increases in nociceptive thresholds in the tail-flick tests (Buhler et al, 2005, Buhler et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now compelling evidence demonstrating that the high-affinity NTS1 subtype is involved in antinociception (Wustrow et al, 1995, Smith et al, 1997, Urban and Gebhart, 1997, Buhler et al, 2005, Sarret et al, 2005, Buhler et al, 2008, Roussy et al, 2008. Thus, microinjection of the selective NTS1 agonist PD149163 into the rostral ventromedial medulla produced increases in nociceptive thresholds in the tail-flick tests (Buhler et al, 2005, Buhler et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was thus conducted to evaluate the implication of NTS1 receptors in opioid-induced analgesia. Since we recently demonstrated that the activation of NTS1 receptors by selective NTS1 agonists reduced the nociceptive behaviors induced by the chemical irritant formalin (Roussy et al, 2008), we used the same experimental model to examine the functional interaction of opioid and NT systems. Specifically, we investigated whether morphine analgesia was affected by NTS1 gene silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, N-methyl-Arg, Lys, Trp, and tert-Leu were substituted for Arg, Arg, Tyr, and Ile, respectively (60-64). Likewise, PD149163, a reduced-amide NT [8][9][10][11][12][13] , showed improved metabolic stability after systemic administration and maintained the analgesic activities of the native NT peptide (65)(66)(67). Subsequently, several additional systemically infused but centrally acting analogs (i.e., NT66L, NT69L, NT79, and ABS212) were synthesized by combining N-terminal modifications and incorporation of non-natural amino acids at positions 8, 9, 11, and 12 (63,64,(68)(69)(70)(71).…”
Section: Figurementioning
confidence: 99%
“…This lack of involvement of opioid systems would be advantageous clinically due to the potential of a reduced abuse liability and the utility of combining neurotensin receptor drugs with other classes of analgesic agents. Although there is general agreement that antinociceptive neurotensin analogs act through neurotensin receptors, it is still uncertain whether these effects are mediated through NTS1, NTS2, or a combination (Boules et al, 2006;Dobner, 2006;Roussy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%